2021
DOI: 10.48550/arxiv.2111.01464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrafast coherent THz lattice dynamics coupled to spins in a van der Waals antiferromagnetic flake

Abstract: A coherent THz optical lattice mode is triggered by femtosecond laser pulses in the antiferromagnetic van der Waals semiconductor FePS 3 . The 380 nm thick exfoliated flake was placed on a substrate and laser-driven lattice and spin dynamics were investigated as a function of the excitation photon energy and sample temperature.The pump-probe spectroscopic measurements reveal that the photo-induced phonon is generated by a displacive mechanism. The amplitude of the phononic signal decreases as the sample is hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This method is particularly effective when competing exchange interactions, for example between ferro-and antiferromagnetic (AFM) contributions, can be tweaked so that a transition between different orders can be achieved. Accordingly, experiments have shown that exchange interactions and anisotropy can be modulated by optically driven phonons which lead to spin reorientation transitions and coherent spin dynamics [96][97][98][99][100][101]. In those studies, both infrared-active and Raman-active phonons have been driven through laser pulses in the terahertz and near visible light spectral ranges.…”
Section: Nonlinear Phononics: Dynamical Control Of Crystal Structuresmentioning
confidence: 99%
“…This method is particularly effective when competing exchange interactions, for example between ferro-and antiferromagnetic (AFM) contributions, can be tweaked so that a transition between different orders can be achieved. Accordingly, experiments have shown that exchange interactions and anisotropy can be modulated by optically driven phonons which lead to spin reorientation transitions and coherent spin dynamics [96][97][98][99][100][101]. In those studies, both infrared-active and Raman-active phonons have been driven through laser pulses in the terahertz and near visible light spectral ranges.…”
Section: Nonlinear Phononics: Dynamical Control Of Crystal Structuresmentioning
confidence: 99%